The unaffordable city: Housing and transit in North American cities. (31st December 2018) - Kramer, Anna
Abstract: This paper presents an empirical analysis of seventeen large American and Canadian metropolitan regions to look at geographies of affordability in transportation and housing. A pre-recession snapshot of frequent transit networks are mapped against housing cost, urban form and socioeconomic variables from census data, and the relationship of housing cost to transit access is tested visually, by descriptive statistics, and with logistic regression. The results show apparent contradictions: while there is great variance in transit access and housing cost between and across cities, transitscapes are consistently more racially diverse, higher density, and poorer than surrounding autoscapes; but, once income and racialization are held constant, there is a decreasing chance of access to transit as housing prices become more affordable. In other words, for many people, there is no affordable access. These paradoxes are interpreted with relevance to patterns of racial and economic geographies of land use and mobility, the dominance of postwar automobility, the suburbanization of poverty, and wealth inequality in North American cities. This research fills gaps in the transit-oriented urban form research, by pointing to the need to consider housing affordability; it also fills gaps in the transit-oriented gentrification research, by opening consideration to all types of transit, not just rail. The results can be compared to relationships of housing affordability and transit in other cities across the world, as there are important commonalities and differences in geographies of poverty and access. While American and Canadian cities are becoming more like international cities in the peripheralization of affordable housing and the mismatch between transit and lower income areas, North American autoscapes face unique challenges to extending public transit access to these peripheries. Understanding and attending to these inequalities of access to housing and transportation can better inform efforts of sustainable transformation through significant mode shift and affordable urban form intensification. Graphical abstract: Highlights: Transitscapes are more diverse and poor, with higher density, older, and more rental housing than surrounding autoscapes. However, when income and other variables are held constant, transitscapes are more likely to have high housing costs. Many affordable suburban areas are underserved by transit. For poor and often racialized people, there is no affordable city. Inequality prevents access to housing and transportation. Securing affordable housing near transit, and extending transit to affordable suburbs, would help.